Physical and Chemical Properties of Gayo Coffee Brewed by Boiling Method with Variation of Particle Coffee Ground - Yufita, Evi; Muhammad Shadiq Maula, Teuku; Gunawati, Gunawati; Lloyd Woodfield, Peter; Yusibani, Elin (Jurnal Ilmu Fisika, 2025)
The effect of coffee ground particle size by the boiling method on the values of physical and chemical parameters is studied. The coffee used is Arabica (Luwak, wine, honey) and Robusta from the Gayo Highlands, Aceh Province, Indonesia. Extraction of the coffee brew uses the boiling method with different particle sizes of coffee grounds (fine and coarse). The caffeine content in the coffee brew is identified using the FieldSpec4 Hi-Res Spectrometer. The particle size of coffee grounds affected the coffee brew's physical properties and caffeine content. The physical properties in the form of the pH value of Arabica coffee brew are lower than Robusta in a range from 4.87 to 4.97 and 5.13 to 5.28, respectively. The pH of coffee brew with fine particle sizes is slightly higher than for coarse ones for Robusta coffee brew. The density of the brew is in the vicinity range of 0.99 g/cm3. Arabica and Robusta brews differ in viscosity and caffeine release, influenced by coffee particle size. Coarse particles yield more caffeine in Arabica, while fine particles release more in Robusta, demonstrating the impact of grind size on caffeine extraction in coffee.